Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Perilaku Pengelolaan Keuangan Karyawan PT Nusantara Card Semesta Kemanggisan: The Influence of Financial Literacy and Financial Attitudes on the Financial Management Behavior of Employees at PT Nusantara Card Semesta Kemanggisan - Putri, Nurhaliza Amalia; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research was conducted at PT Nusantara Card Semesta Kemanggisan with the aim of analyzing the influence of financial literacy (X1) and financial attitudes (X2) on the financial management behavior (Y) of card division employees at PT Nusantara Card Semesta Kemanggisan. Data were collected through a survey of 72 card division employees using a questionnaire with a non-probability sampling technique using saturated samples. The method used in this research is a quantitative approach using IBM SPSS Statistic V. 26 software. The results of the study concluded that: 1) Financial literacy (X1) has a partial effect on financial management behavior (Y). 2) Financial attitudes (X2) have a partial effect on financial management behavior (Y). 3) Financial literacy (X1) and financial attitudes (X2) have a simultaneous effect on financial management behavior (Y) of card division employees at PT Nusantara Card Semesta Kemanggisan.